Hubungan Paritas, Umur Ibu Dengan Perdarahan Post- Partum Primer di Rumah Sakit Panti Rapih Yogyakarta Tahun 2017- 2018 - Theresia Heni Lestari; Theresia Endah Marianingsih; Yuliasti Eka Purnamaningrum (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: The cause of AKI in DIY 2018, 11% of post-partum hemorrhage, with a gap in MMR target and achievement <102 / 100,000 live births, MMR in 2018: 111.5 / 100,000 live births, indicating an increase in MMR. In the same year at Panti Rapih Hospital, there was an increase in the incidence of post-partum hemorrhage by 6%, with 62.8% of parity at risk, 53.5% of age at risk. Objective: of the study was to determine the relationship between parity and maternal age with the incidence of primary post-partum hemorrhage at Panti Rapih Hospital in 2017-2018. Methods: observational, cross sectional design, sample 43 people. Chi Square Test data analysis. Results: There was a significant relationship between parity and the incidence of primary post partum hemorrhage (p-value = 0.011). There was a significant relationship between age and the incidence of primary post-partum hemorrhage at Panti Rapih Hospital (p-value = 0.014). Conclusion: There is a significant relationship between parity, maternal age <20 years or> 35 years with the incidence of primary post partum hemorrhage at Panti Rapih Hospital in 2017-2018.